2016
DOI: 10.1038/nprot.2016.087
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of biomimetic photoresponsive polymer springs

Abstract: Polymer springs that twist under irradiation with light, in a manner that mimics how plant tendrils twist and turn under the effect of differential expansion in different sections of the plant, show potential for soft robotics and the development of artificial muscles. The soft springs prepared using this protocol are typically 1 mm wide, 50 μm thick and up to 10 cm long. They are made from liquid crystal polymer networks in which an azobenzene derivative is introduced covalently as a molecular photo-switch. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
51
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 34 publications
0
51
0
Order By: Relevance
“…Here, the gradient is established primarily during the first polymerization step, which means that the extent of cross‐linking is greater at the top of the cell than at the bottom of the cell. The more densely cross‐linked areas will always be found at the outside of the curvature because they are stiffer 20. Gradients in stiffness have also been reported in twisting plant elements, and the combination of this gradient with a curvature plays a role in determining the handedness of biological helices 32, 33…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the gradient is established primarily during the first polymerization step, which means that the extent of cross‐linking is greater at the top of the cell than at the bottom of the cell. The more densely cross‐linked areas will always be found at the outside of the curvature because they are stiffer 20. Gradients in stiffness have also been reported in twisting plant elements, and the combination of this gradient with a curvature plays a role in determining the handedness of biological helices 32, 33…”
mentioning
confidence: 99%
“…The variety of movements seen in the plant and animal kingdoms have provided inspiration for the engineering of soft robots of all kinds,9, 10, 11, 12, 13, 14 and in particular, the realization that plant mechanics often rely on dynamic helical systems15, 16, 17, 18, 19 has motivated the development of a variety of chiral actuators where molecules were used either as active transducers of energy11, 13, 20, 21 or as relays for humidity or temperature changes 22, 23, 24, 25. These soft actuators have demonstrated reversible shape transformation, work, and motility,26 but the response speed and power produced remain moderate, mainly owing to the lack of mechanisms to drive non‐linear actuation 27.…”
mentioning
confidence: 99%
“…Experiments and theory revealed these ribbons form curly helicoid/spiral morphologies and switch helical sense with temperature10. Recently, Katsonis and coworkers1112 synthetized biomimetic photo-responsive elastic springs whose actuation is encoded by a 90-degree-twist liquid crystalline microstructure with different angular orientation. They observe a variety of morphologies given liquid crystal polymer composition and asymmetry sources such as: twist handedness, angular offset of the mid-plane director and gradient in crosslinking density along the sample thickness.…”
mentioning
confidence: 99%
“…This actuation can be reversed by exposing the material to visible (VIS) light or heat, which accelerate the cis azobenzenes to fall back to the trans state. The current consensus in experimental [5,[7][8][9] and theoretical studies [10][11][12][13] is that the amplitude of the photoinduced deformation is related to the statistical building up of molecules in the cis state. However, a recent experimental study [14] has revealed that this is only one side of the story.…”
mentioning
confidence: 99%
“…Light-activated systems are especially advantageous for remote control as their application does not require built-in electrodes and heating devices as in electrically or thermally actuated materials. The probably most-studied light responsive systems are liquid crystal (LC) polymers copolymerized with azobenzene [1][2][3][4][5][6]. Azobenzene functions as a photoisomerizable molecule that is covalently embedded in the LC polymeric skeleton and absorbs ultraviolet (UV) light leading to a transition from a rodlike trans state into a bentlike cis state.…”
mentioning
confidence: 99%